Answer:
Solving for the variable, x:
![x = (1)/(3)y + (2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/xgzc46ac04u5yzl3eb2n1ganzyquh3h7g8.png)
Solving for the variable, y:
![y = 3x - 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/fj6z3fjxvkgseivilnqrjv0eb3pcos4xny.png)
Explanation:
IF:
You are solving for the variable, x. Note the equal sign, what you do to one side, you do to the other. Isolate the variable, x. First, follow PEMDAS, then do the opposite of PEMDAS.
First, distribute 2 to all terms within the parenthesis:
(3x - y = 2) * 2 = (6x - 2y = 4)
Next, solve for x. Add 2y to both sides:
6x - 2y (+2y) = 4 (+2y)
6x = 4 + 2y
Next, divide 6 from both sides:
(6x)/6 = (4 + 2y)/6
x = (2y)/6 + (4)/6
x = (1/3)y + (2/3)
IF:
You are solving for the variable, y. Note the equal sign, what you do to one side, you do to the other. Isolate the variable, y. First, follow PEMDAS, then do the opposite of PEMDAS.
First, distribute 2 to all terms within the parenthesis:
(3x - y = 2) * 2 = (6x - 2y = 4)
Next, solve for y. Subtract 6x from both sides:
6x - 2y = 4
6x (-6x) - 2y = 4 (-6x)
-2y = -6x + 4
Then, divide -2 from both sides:
(-2y)/-2 = (-6x + 4)/-2
y = (-6x)/-2 + (4)/-2
y = 3x + (-2)
y = 3x - 2
~